2015
DOI: 10.5539/gjhs.v7n7p106
|View full text |Cite
|
Sign up to set email alerts
|

Health System’s Responsiveness of Inpatients: Hospitals of Iran

Abstract: Introduction:Additional to improving health and ensuring equitable financing that are two predominant goals of health system, another important goal of health systems is responsiveness to people’s non-medical expectations. In this study we try to assess the health system’s responsiveness in academic and non-academic hospitals.Methods:This is a cross sectional study done in summer 2014 in Mashhad-Iran, we surveyed a total number of 403 inpatients by multi-stage sampling. A questionnaire of responsiveness and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
4
18
2
Order By: Relevance
“…This finding was similar to the reports of other previous studies (9,(25)(26)(27). Therefore; public hospitals must compete to private hospitals in terms of good service delivery.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 82%
“…This finding was similar to the reports of other previous studies (9,(25)(26)(27). Therefore; public hospitals must compete to private hospitals in terms of good service delivery.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 82%
“…The result was in agreement with the findings of other studies in Iranian public hospitals (4)(5)(6). Improvement of service delivery in the Iranian public health sector, after implementation of HSEP could be considered as a reason.…”
Section: Discussionsupporting
confidence: 83%
“…Bazzaz et al reported that dignity had the highest score in public centers and quality of basic amenities had the highest score in private centers. The health care responsiveness score was higher in private than other public and charity medical center ( 13 ). Peltzer and Kavosi showed that Communication, autonomy, and discriminatory experiences were key areas to improve responsiveness of health services in South Africa ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 97%